Does risperidone causes life threatening pancytopenia? A case report from Nepal (Bangladesh Critical Care Journal, 2023)
Antipsychotic drugs like risperidone are sometimes associated with rare but serious adverse events such as pancytopenia. We describe a 38-year-old man on risperidone for schizophrenia for two months who experienced pancytopenia. There was no prior history of hematological diseases or contact with possible triggers in the patient. Upon admission, he presented with symptoms of generalized weakness, black stool, constipation, and recurrent urinary tract infection. Risperidone was promptly discontinued, and supportive measures including prophylactic antibiotics, blood transfusion, and colony-stimulating factors were initiated. Close hematological monitoring should be considered in patients on risperidone, and awareness of the potential risk of pancytopenia associated with its usage is crucial. Timely identification and management of drug-induced pancytopenia are crucial to ensure favorable patient outcomes and prevent potentially life-threatening complications.Bangladesh Crit Care J September 2023; 11 (2): 133-136